2022
DOI: 10.1021/acs.jpcb.2c02862
|View full text |Cite
|
Sign up to set email alerts
|

Domain Size Regulation in Phospholipid Model Membranes Using Oil Molecules and Hybrid Lipids

Abstract: The formation of domains in multicomponent lipid mixtures has been suggested to play a role in moderating signal transduction in cells. Understanding how domain size may be regulated by both hybrid lipid molecules and impurities is important for understanding real biological processes; at the same time, developing model systems where domain size can be regulated is crucial to enable systematic studies of domain formation kinetics and thermodynamics.Here, we perform a model study of the effects of oil molecules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 108 publications
0
9
0
Order By: Relevance
“…These cases exhibited a gradual evolution in the contact angle, increasing far beyond typical measurements for membranes formed in hexadecane , and in some cases reaching as high as 80°. The behavior continued for as long as 2 h after formation and appears to occur at a similar time scale to the growth of lipid domains observed by Scheidegger . A sample video of this evolution with respect to time is provided in Video S1.…”
Section: Resultsmentioning
confidence: 99%
“…These cases exhibited a gradual evolution in the contact angle, increasing far beyond typical measurements for membranes formed in hexadecane , and in some cases reaching as high as 80°. The behavior continued for as long as 2 h after formation and appears to occur at a similar time scale to the growth of lipid domains observed by Scheidegger . A sample video of this evolution with respect to time is provided in Video S1.…”
Section: Resultsmentioning
confidence: 99%
“…It has been observed that bilayers formed from phospholipids dispersed in squalene exhibit very high specific capacitance values, indicative of a thin “solvent-free” bilayer. That is because such a large hydrophobic molecule will experience a high entropic penalty in its interactions with lipid acyl chains and tend to be largely excluded from the bilayer. Any residual squalene in the bilayer would be most probably oriented parallel to the membrane plane (i.e., between its two leaflets), as seen by neutron diffraction measurements, and not situated at the water-lipid interface …”
Section: Resultsmentioning
confidence: 99%
“…Any residual squalene in the bilayer would be most probably oriented parallel to the membrane plane (i.e., between its two leaflets), as seen by neutron diffraction measurements, and not situated at the water-lipid interface. 74 Also shown in Table 2 are the interfacial parameters for cholesterol-enriched membranes (DOPC:chol at 1:1 mole ratio) in the presence of ASA, which can be compared to the analogous case of cholesterol-free DOPC. Similar effects are seen upon inclusion of ASA as with chol-free bilayers, but with a somewhat diminished intensity.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This approach to determining the modulus yields consistent values for DOPC (~10 5 Pa) [ 22 , 23 ] that are an order of magnitude lower than those reported in other systems [ 27 ] when hexadecane is used as the oil solvent. We suspect that this is partially due to the impact of residual oil molecules within the membrane, which causes the membrane thickness to swell [ 23 , 28 , 29 , 30 ], and also in part due to the membrane area (and therefore, volume) changing during compression. When squalene is used as the oil solvent, membrane thicknesses approach the solvent-free limit and measured Young’s moduli (~10 6 Pa) are on the same order of magnitude as solvent-free approaches; however, the moduli values are still on the lower edge of the range, indicating possible remaining contributions from the membrane area (volume) changes during compression.…”
Section: Resultsmentioning
confidence: 99%